Effect of variation in incubation temperature and exposure to extreme temperature on the hatchability of Nile crocodile (Crocodylus niloticus) eggs - Brown, Geoff (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2022.